Muzyczne komponenty dramatu mimicznego Skrzypek Opętany Bolesława Leśmiana - Suchowiejko, Renata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
Bolesław Leśmian’s The Mad Violinist contains many suggestions concerning the musical side of the drama, especially its properties of sound and expression. The violin and violin playing fulfill an important function – coloristic, dramaturgic and symbolic – in the work. Also appearing are the sounds of other instruments (gong, dulcimer, plucked string instrument), refined musical timbres and acoustic effects (sound portrait of the Woodland Water Nymph), musical profiling of the characters (Alaryel plays the violin, Chryza dances on stilts, the Witch strikes the clock) and ‘ballet’ scenes – solo and ensemble (Chryza’s dance, Chryza and the Water Nymph’s dramatic duet, the dance suite in the Second Delusion).The poet also described very suggestively the expressive categories of the fragments set to music. Their skillful distribution in time and combination on a contrast principle, as well as the utilization of their dramatic potential, contribute to the reinforcement of their power of expression. Alaryel’s virtuoso showpiece, maintained in a furioso-type tone, leads to a true explosion of sound and contrasts with the lyrical and wistful lamentoso played over the grave of the Water Nymph. However, the ethereal timbre of the Water Nymph, who is accompanied by an indigo dawn, emphasizes the symbolic significance of this character. The musical components in The Mad Violinist blend perfectly with the other elements – word, gesture, stage movement and the visual side of the drama, creating an extraordinary whole of great artistic value.The present article also proposes a reference to the violin music of Belgian violinist and composer Eugène Ysaÿe, whose oeuvre fits into the European Symbolist trend. His Six Sonatas for Violin Solo op. 27 from 1927 form a peculiar interpretative context for Leśmian’s drama. The point here is not to suggest any actual relationship, but rather to draw attention to the similar type of artistic sensitivity and imagination, feel for color and deeply sensual manner of experiencing the world.